Tahrim süresinde aile içi ilişkiler - Işık, Bilal (My University, 1999)
Tahrim sûresi Medine'de nâzil olmuş, oniki ayetten oluşan bir sû-redir. Sûrenin ana konusu ailenin korunması üzerinde yoğunlaşmak-tadır. Nuzûl sebepleri ile ilgili beş rivayet bulunmaktadır. Tefsir ve hadis usûlü kurallarına göre, bunların en sahihi ve sûrenin nuzûl sebebi ol-maya uygun olanı bal hadisidir. Medine'de nâzil olan Ahzâb, Talak ve Mülk sûreleriyle şekilsel ve muhteva yakınlığı bulunmaktadır. İlk beş ayette Peygamber'e yapılan itap, ayetlerle ilgili fıkhî görüş farklılıkları, peygamberlik makâmının önemi, ailenin filolojik yapısı ve modern zamanlarda ailenin karşılaştığı güçlükler konu edinilmiştir. Daha sonra boşanmanın doğuracağı tehlike, Peygamber'in hanımları ve tarih boyunca çok evlilik uygulaması işlenmiştir. VI ve VIII. ayetlerden oluşan sonraki pasajda çocuk terbiyesi, çocukların cinsel terbiyesi ile televizyon konusu ele alınmıştır. Çocuklara kuralları dahilinde cinsel terbiye verilmesinin önemi belirtilmiştir. Bu süreçte televizyon ve daha başka görsel yayınlarının çocuk için zararlı olabileceği anlatılmıştır. IX. ayette münafıkların bu süreçte bozguncu faaliyette buluna-cakları ve Peygamber'in onlarla uygun şekilde mücadelesi emri izah e-dildi. X ve XII. ayetlerde ise Nuh ve Lut'un eşlerinin iman etmedikleri sürece, peygamber eşi olmalarının kendilerine bir şey kazandırmaması; Firavunun eşiyle, Hz. Meryem'in inançlarındaki sebat ve bu uğurda karşılaştıkları zorluklara direnmeleri ferdi mesuliyet başlığı altında in-celenmiştir. The chapter of Tahrim, as a part of the Holy Quran, contains 12 verses and was revealed in Madina. The main theme of this chapter focuses on the protection of family order. There are five rumours about why this chapter was revealed. According to the Tafsir and Hadith resources, the most authentic one out of five rumours is the one called Bal Hadith. This one is also suitable with the content of the chapter. This chapter has links with the Ahzab, Talak and Mulk chapters of the Holy Quran in manner and content. In the first five verses we dealt with the scolding of God to the Prophet, different opinions of the jurists about these verses, importance of the post of the prophethood, philological structure of the family and difficulties that the family has encountered in modern times. Then we touched on the dangers of the divorce, wives of the Prophet and polygamy practice in the past generations. The importance of the sex education to teach the children within its borders was also mentioned. In the education process we attracted attention to the point that television and other visual broadcasting means may have unwanted influences upon the children. In the 9th verse of the Tahrim chapter, Prophet was given the information that hypocritical people may have conspiracy plans, so he should fight against them in appropriate manner. 10th and 11th verses explain that the wives of the prophet Noah and Lut failed to believe their husbands, so they gain nothing even their husbands are the messengers of the God. On the contrary, the wife of Firavun and Maria became believers of God, persevered their beliefs and withstood the difficulties they encountered for the sake of God. We discussed these two opposite examples of above-mentioned people under the topic individual responsibility of the persons.
Keywords: Aile içi ilişkileri; Ayetler ve sureler (Kuran); Din; İslam Dini; Kur’an ve Kur’an İlimleri